PENERAPAN TEKNIK PROBLEM SOLVING DALAM KONSELING KELOMPOK - Erlindawati Erlindawati; Silvianetri Silvianetri (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
Humans are often faced with various problems. Problems can be understood as one part of any struggle that every human being cannot avoid. Every problem sometimes feels very heavy, so many people feel very miserable when they get problems. Some even choose to end their lives because of their inability to survive and face the problems at hand. The purpose of this writing is to know the application of problem solving techniques in group counseling in alleviating student problems so that there are decisions that must be taken by someone in alleviating problems. Based on the results of several studies related to the results of discussions on the application of problem solving techniques in group counseling is very effective in solving the problems of students or other adolescents by going through procedures or stages in the implementation of problem solving.it can be seen from several studies that compare before and after being given group counseling services.